KEPEMIMPINAN PEREMPUAN PERSPEKTIF HADIS - Fatmawati, Fatmawati (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2015)
Many groups are calling to apply the Islamic values. Both in social issues, economy, country and politics. But they are not able to create a balancing of the values of Islam itself. Because in general, they actually limit the scope of women's movement. They do not give chance to women to participate in the world holding the reins of supreme leadership.If the excuse put forward is that Islamic values can be applied in general, why not give the right to limit even to women? In fact Islam devoted to men and women.However, when the raging spirit has been created, the power has been awakened, when the women had to roll up his sleeves to participate in social, political and matters relating to life, why the sudden sheet of voiced speech with a loud "O woman returned to the house each of you ", an appeal which it seems so unfair to discredit. Therefore, re-examine the traditions that are considered to discredit the woman, for Hadith Prophet Muhammad saw. ill only textually but also interpreted in context is the right thing to do.